2021
DOI: 10.1097/corr.0000000000001793
|View full text |Cite
|
Sign up to set email alerts
|

Is the Preoperative Use of Antidepressants and Benzodiazepines Associated with Opioid and Other Analgesic Use After Hip and Knee Arthroplasty?

Abstract: Background Mental health disorders can occur in patients with pain conditions, and there have been reports of an increased risk of persistent pain after THA and TKA among patients who have psychological distress. Persistent pain may result in the prolonged consumption of opioids and other analgesics, which may expose patients to adverse drug events and narcotic habituation or addiction. However, the degree to which preoperative use of antidepressants or benzodiazepines is associated with prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Excluding the oldest population in a restriction analysis further increased the aOR for history of psychiatric disease, indicating that the impact of psychiatric disease as a risk factor for new postoperative prolonged opioid use is stronger in younger patients (online supplemental table 4). In line with this, other studies have found an association between preoperative benzodiazepine or antidepressant use and prolonged postoperative opioid consumption 10 18. Our results, alongside aforementioned studies, indicate that clinicians must be aware of this relationship when prescribing postoperative opioids.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Excluding the oldest population in a restriction analysis further increased the aOR for history of psychiatric disease, indicating that the impact of psychiatric disease as a risk factor for new postoperative prolonged opioid use is stronger in younger patients (online supplemental table 4). In line with this, other studies have found an association between preoperative benzodiazepine or antidepressant use and prolonged postoperative opioid consumption 10 18. Our results, alongside aforementioned studies, indicate that clinicians must be aware of this relationship when prescribing postoperative opioids.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this, other studies have found an association between preoperative benzodiazepine or antidepressant use and prolonged postoperative opioid consumption. 10 18 Our results, alongside aforementioned studies, indicate that clinicians must be aware of this relationship when prescribing postoperative opioids.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Orthopaedic surgeons also need to be aware of the prevalence of benzodiazepine prescrip-tions among their patients. Studies have found that 5.6% to 12% of patients undergoing total knee arthroplasty were taking benzodiazepines within 6 months prior to surgery 8 . Hozack et al found that 12% of patients undergoing upper extremity surgery had filled a benzodiazepine prescription within 6 months prior to surgery 9 , while Kha et al found that 16% of patients having lumbar decompression had filled a prescription within 8 months preoperatively 10 .…”
mentioning
confidence: 99%